Penerapan Pembelajaran Problem Based Learning untuk Meningkatkan Literasi Matematis Siswa Kelas X di SMA Muhammadiyah 5 Dukun - Khurin’in Khurin’in; Nur Fauziyah; Sri Suryanti (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Mathematical literacy is an important ability for students, this ability is still considered low. The PBL (Problem Based Learning) model is an alternative learning model that can improve students' mathematical abilities. The aim of this research is to find out how students' mathematical literacy abilities are both before and after using the problem-based learning model. They also want to know how students interact with the problem-based learning process. The method in this research is a quasi-experimental method with the design used being a pretest and posttest non-equivalent control group design. The population in this study were class X students of SMA Muhammadiyah 5 Dukun for the 2023/2024 academic year. The research instruments used were questions describing tests of mathematical literacy skills and questionnaires on student responses to the learning being implemented. The data analysis technique uses quantitative data analysis. The research results show that from the t test results above the sig value (2 tailed) is 0.000 < 0.05 because the significant value is 0.000 < 0.05, indicating that students' mathematical abilities can be improved by implementing problem-based learning.